Analisis Penyerapan Tenaga Kerja Dalam Sektor Industri Besar dan Sedang di Sumatera Barat - Sulthana, Yusuf Galih; Ariusni, Ariusni (Universitas Negeri Padang, 2024)
This research aims to find out and analyze; (1) how big is the influence of GRDP on labor absorption in large and medium industries in West Sumatra, (2) how big is the influence of wages on labor absorption in large and medium industries in West Sumatra, (3) how big is the influence of the number of companies on labor absorption large and medium industries in West Sumatra, (4) how big is the influence of GDP, wages and number of companies on labor absorption in large and medium industries in West Sumatra. This type of research is descriptive and associative research. The data used is panel data with the 2017-2020 time series and cross section of 19 19 districts and cities in West Sumatra sourced from the Central Statistics Agency (BPS). The method used in this research is panel data regression analysis using a fixed effect model approach assisted by Eviews 9 software. The results of this research show that; (1) GRDP has a positive and significant influence on the employment of large and medium industries in West Sumatra (2) wages have an insignificant influence on the employment of large and medium industries in West Sumatra (3) the number of companies has a significant influence on labor absorption in large and medium industries in West Sumatra (4) the number of companies, wages and GRDP together have a significant effect on labor absorption in West Sumatra.